2020
DOI: 10.1136/bjsports-2020-102315
|View full text |Cite
|
Sign up to set email alerts
|

Injuries and illnesses among competitive Norwegian rhythmic gymnasts during preseason: a prospective cohort study of prevalence, incidence and risk factors

Abstract: ObjectivesRhythmic gymnastics is an Olympic sport that demands high training volume from early age. We investigated the extent of, and risk factors for, injuries among competitive Norwegian rhythmic gymnasts.MethodsOne hundred and seven of 133 (80.5%) female rhythmic gymnasts (mean age: 14.5 years (SD 1.6), mean body mass index: 18.9 (SD 2.2)) participated. All gymnasts completed a baseline questionnaire and the ‘Triad-Specific Self-Report Questionnaire’. Injuries, illnesses and training hours were recorded pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
(56 reference statements)
2
12
2
Order By: Relevance
“…Compared with studies employing the same methodology in other sports, our findings were in line with observations by Pluim et al 21 (average weekly prevalence of health problems, 21%; substantial health problems, 15%) and Clarsen et al 11 (36% and 15%, respectively), but lower than those of Moseid et al 18 (43% and 25%, respectively) and Gram et al 14 (39% and 28%, respectively). However, the participant profile differs substantially between these studies: Clarsen et al 11 monitored adult Olympic athletes from mixed sports; Pluim et al, 21 11-to 14-year-old elite tennis players; Moseid et al, 18 a 15-to 16-year-old mixed group of youth athletes attending sports academy high schools, and Gram et al, 14 female rhythmic gymnasts. In our study, the average weekly prevalence of all acute injuries reported was 10% and the average weekly prevalence of substantial acute injuries was 7%.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with studies employing the same methodology in other sports, our findings were in line with observations by Pluim et al 21 (average weekly prevalence of health problems, 21%; substantial health problems, 15%) and Clarsen et al 11 (36% and 15%, respectively), but lower than those of Moseid et al 18 (43% and 25%, respectively) and Gram et al 14 (39% and 28%, respectively). However, the participant profile differs substantially between these studies: Clarsen et al 11 monitored adult Olympic athletes from mixed sports; Pluim et al, 21 11-to 14-year-old elite tennis players; Moseid et al, 18 a 15-to 16-year-old mixed group of youth athletes attending sports academy high schools, and Gram et al, 14 female rhythmic gymnasts. In our study, the average weekly prevalence of all acute injuries reported was 10% and the average weekly prevalence of substantial acute injuries was 7%.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding prevalence of health problems, we found that at any given time, 40% of the young football players experienced a health problem, and 19% experienced a substantial health problem. These numbers compare well with other studies on adolescent athletes [ 2 , 17 , 18 , 24 , 25 ], which have reported that approximately half of the reported health problems among adolescent athletes are substantial. In terms of response rate, we observed an overall low response rate.…”
Section: Discussionsupporting
confidence: 89%
“…This is also the first study to report the prevalence of injury in trampoline gymnasts. The average weekly prevalence of reported injury was lower than previously reported in competitive, rhythmic gymnasts (Gram et al, 2020). When gymnasts were grouped into growth spurt status (pre, circa & post growth spurt), an injury was more prevalent in gymnasts circa-growth spurt compared to those pre-and post-growth spurt.…”
Section: Discussioncontrasting
confidence: 54%